Diffusion coefficients in aqueous solutions of potassium chloride at high and low concentrations - Lobo, Victor M. M. (1998)
Differential diffusion coefficients of potassium chloride in water at 298.15 K, and at concentrations from 0.001 M to 1 M, have been measured using a conductimetric cell and an automatic apparatus to follow diffusion. The results are discussed on the basis of the Robinson and Stokes, Onsager-Fuoss and Pikal models. The cell uses an open-ended capillary method and a conductimetric technique is used to follow the diffusion process by measuring the resistance of a solution inside the capillaries, at recorded times.